Rapid prototyping test bed of TS-Fuzzy MPPT controller - Ajaamoum, Mohamed (International Review on Modeling and Simulations, 2019)
This paper presents the design and development of an experimental rapid prototyping platform. This platform will be exploited in the study of the Takagi-Sugeno fuzzy control ("TS -fuzzy ") enabling the Maximum Power Point Tracker (MPPT) of photovoltaic (PV) systems. In this this study, the platform is composed of four elements in its material target part: the photovoltaic emulator (PVE), PWM (Pulse With Modulation) generator, a Buck-Boost converter. The software part Matlab/ Simulink supplies the control signal via an acquisition card. This paper discusses the different steps in the design, simulation and realization of the S- fuzzy logic controller. The results from the experiment support the performance of the controller and validate its effectiveness.